Prevalence and correlates of non-daily and daily cannabis use among persons 15 years and older in South Africa: results of a national survey in 2017 - Shandir Ramlagan; Karl Peltzer; Supa Pengpid (BMC, 2021)
Abstract Background The study aimed to assess the prevalence and correlates of non-daily and daily cannabis use among persons 15 years and older in South Africa. Method In a national cross-sectional 2017 survey, 39,207 persons 15 years and older (Median = 34 years) responded to a questionnaire on cannabis use and health variables. Multinominal logistic regression was used to assess the determinants of nondaily and daily cannabis use among the general population and logistic regression for the determinants of daily cannabis use among active cannabis users. Results Results indicate that 5.0% of the participants engaged in non-daily and 2.8% in daily cannabis use in the past 3 months. In adjusted multinomial logistic regression analysis, male sex, Grade 8-11 education, Coloureds, alcohol use disorder, never married, and other drug use were positively associated with daily cannabis use while not in not labour force was negatively associated with daily cannabis use. Moreover, male sex, never married, alcohol use disorder, and other drug use were positively, while physical multimorbidity was negatively associated with nondaily cannabis use. In adjusted logistic regression, compared to nondaily cannabis users, daily cannabis users were more likely male and were less likely not in the labour force and were less likely using other drugs. Conclusion About one in ten participants had used cannabis in the past 3 months in South Africa. Several sociodemographic and health indicators were identified that were associated with non-daily and/or daily cannabis use.